Gender Differences in How Family Income and Parental Education Relate to Reading Achievement in China: The Mediating Role of Parental Expectation and Parental Involvement - Guo, Xiaolin; Lv, Bo; Zhou, Huan; Liu, Chunhui; Liu, Juan; Jiang, Kexin; Luo, Liang (Frontiers in Psychology, 2018)
The impact of social economic status (SES) on children’s academic outcomes has been well documented. However, the mechanisms underlying this relationship remain poorly understood. Furthermore, the process by which SES relates to academic achievement needs to be studied separately for boys and girls. Using a sample of 598 Chinese children (299 boys, 299 girls) in grades 4 to 6 and their parents, this study examined the process of how family SES, specifically family income and parental education, indirectly relates to children’s reading achievement through parental expectation and parental involvement and whether this process differs between boys and girls. The results revealed that parental expectation and specific parental involvement behaviors played critical mediating roles between family SES and reading achievement and, more importantly, that the exact nature of these links differed by the gender of children. For boys, both the effect of parental education and the effect of family income were partially mediated by parental expectation and parent-child communication orderly. For girls, the effect of parental education was partially mediated by three separate pathways: 1) home monitoring; 2) parent-child communication; and 3) parental expectation followed by parent-child communication, while the effect of family income was fully mediated by parent-child communication. These findings suggest a process through which SES factors are related to children’s academic development and identify a context under which these associations may differ. The practical implications of these findings are discussed, along with possible future research directions.